Redewiedergabe in verschiedener Form - ein Vergleich Deutsch-Norwegisch - Solfjeld, Kåre (HERMES - Journal of Language and Communication in Business, 2009)
The subject of the present empirical study – based on both ﬁctional texts and newspaper texts – is direct and indirect reported speech in German and Norwegian. The focus of the study is the broader range of structural possibilities for marking reported speech in German, for instance the subjunctive mood, which can be exploited to signal reported speech in syntactically independent sentences, i.e. on discourse top-level, in a way that is not possible in Norwegian. The study shows that the structural differences create different possibilities in German and Norwegian for identifying propositions as having another origin than the actual speaker/writer. Generally, Norwegian readers must rely on pragmatic inferences to a higher degree than German readers in order to identify the source. Furthermore, direct reported speech is more frequent in the Norwegian than in the German newspaper texts.